018 One-year prognosis after syncope and the failure of the ROSE decision instrument to predict 1-year adverse events. (14th September 2011) - Henderson, S S; Reed, M J; Newby, D E; Gray, A J
Abstract : Objectives and Backgrounds: (1) To investigate the incidence of adverse events at 1-year in the cohort of Emergency Department (ED) syncope patients enrolled in the original ROSE study; (2) To investigate the time to adverse event; and (3) To investigate the test performance of the ROSE decision instrument to detect events at 1-year. Methods: This report details the 1-year follow-up of adult syncope patients presenting to the ED who were enrolled into the ROSE study, a single centre, prospective, observational cohort study. The primary end point was the combination of serious outcome (SO) and all-cause death (ACD) at 1 year. SO encompassed acute myocardial infarction, life-threatening arrhythmia, need for pacemaker/implantable defibrillator, pulmonary embolus, cerebrovascular accident, intracranial or subarachnoid haemorrhage, interventional procedure or haemorrhage requiring blood transfusion. Secondary endpoints were ACD and cardiovascular SO at 1 year. Results: 1043 patients were available for analysis; 162 patients (15.5%) had a primary outcome. 28 (17%) of these were within 24 h, 56 (35%) were within 1 week and 77 (48%) were within 1 month. The remaining 85 (52%) outcomes occurred between months 2 and 12. At 1 year, 71 (6.8%) patients had died and 76 (7.3%) had a cardiovascular SO. The sensitivity and specificity of the ROSE decision instrument for 1-year SO and ACD was 71.6% (63.9–78.3) and 71.1% (67.9–74.0), for 1-year ACD was 76.1% (64.2–85.1) and 67.4% (64.3–70.3) and for 1-year cardiovascular SO was 75.0% (63.5–83.9) and 67.5% (64.5–70.5). Conclusions: The proportion of patients with SO and ACD 1 year after syncope is similar to recent international syncope studies. We have defined the proportion of patients with cardiovascular SO at 1-year, and have shown that most events occurred in the first month with decreased frequency of events noted after that time frame especially marked for cardiovascular SO. More than 50% of the outcomes observed however occurred after the first month. The ROSE decision instrument does not perform well at predicting 1-year outcome of ED syncope patients.